2013
DOI: 10.1073/pnas.1318001111
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanisms of PriA-mediated DNA replication restart

Abstract: Collisions between cellular DNA replication machinery (replisomes) and damaged DNA or immovable protein complexes can dissociate replisomes before the completion of replication. This potentially lethal problem is resolved by cellular "replication restart" reactions that recognize the structures of prematurely abandoned replication forks and mediate replisomal reloading. In bacteria, this essential activity is orchestrated by the PriA DNA helicase, which identifies replication forks via structure-specific DNA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
206
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(212 citation statements)
references
References 47 publications
5
206
1
Order By: Relevance
“…This feature appears to arise from the juxtaposition of motif II and the ARL within RecQ enzymes. A similar motif II-ARL arrangement is present in the SF2 PriA DNA helicase (39), indicating that the DNA-dependent changes observed in RecQ could apply to other DNA helicase families as well.…”
Section: Discussionmentioning
confidence: 74%
“…This feature appears to arise from the juxtaposition of motif II and the ARL within RecQ enzymes. A similar motif II-ARL arrangement is present in the SF2 PriA DNA helicase (39), indicating that the DNA-dependent changes observed in RecQ could apply to other DNA helicase families as well.…”
Section: Discussionmentioning
confidence: 74%
“…Although our analysis does not allow evaluation of these transitions directly, we observe that the stimulation of HsPol ␥ activity corresponds with a transition from the collapsed to a less dense species. Interestingly, recent studies on replication restart in bacteria have shown that the 65-nt binding mode can be reverted actively to the 35-nt binding mode by interaction with the protein machinery required for reinitiating prematurely terminated replication (42). Despite its similar DNA binding affinity and mode of DNA binding, HsmtSSB stimulates Pol ␥ activity and facilitates template DNA opening at concentrations exceeding that required for template saturation, whereas for DmSSB and EcSSB, template saturation corresponds roughly to the maximal stimulation phase and the transition from partially to fully open template molecules.…”
Section: Discussionmentioning
confidence: 99%
“…SSB 35 is associated with DNA replication, and SSB 65 is associated with DNA repair. Single-molecule experiments have shown that both PriA and PriC promote shifting of the SSB binding mode from SSB 65 to SSB 35 (44,53). It was proposed that PriA and PriC might thus release a small region of ssDNA where DnaC can load DnaB.…”
Section: Biochemistry Of Pria and Its Partnersmentioning
confidence: 99%
“…A full-length structure of PriA from K. pneumoniae with 88% identity with E. coli PriA and the ability to complement PriA mutants of E. coli revealed a structure with six tightly clustered domains (53). The first domain has been crystallized before from the E. coli protein and shown to be able to bind the 3=-OH group of ssDNA (41).…”
Section: Biochemistry Of Pria and Its Partnersmentioning
confidence: 99%